Os Mbyá vão à escola : uma etnografia sobre os sentidos da escola na aldeia da Estiva - Carreira, Luiz Fernando Stumf (2015)
This dissertation presents an analysis of the Guarani-Mbyá school and its goal is to understand how the Guarani think and give meaning to the school institution introduced in the village. Therefore, the text emphasizes in its analysis how indigenous construct, transmit and acquire knowledge, correlating them with the kind of teaching and learning process favored by the school. This is an ethnographic study of the school of Estiva, village in the municipality of Viamão / RS. The study has its starting point in the growing indigenous movement toward the school, a move that seems to point the way they understand it. The speeches of the older members of the village show their concern about appropriating the powers of white man‟s world (its technology, bureaucracy and legal aspects, for example) which are fundamental to the survival of Guarani communities nowadays. In this sense, the school appears as an apprehension space of this other world aspects that are interesting and necessary to indigenous and which refer directly to the way they deal with otherness. Thus, the centrality given to Guarani processes of learning another "culture" refers to the analysis of the school according to classical topics of ethnology and corporality in the indigenous relationship with the white man. The cannibalistic predation, such as contact strategy appears as central key discussion I propose. The school, presented on this paper, while world's appropriation of white man‟s space, seems to take to the Mbyá a fundamental importance regarded to the possibility of incorporation of the Other, that is, white man